Prevention of Higher Education Radicalism in Aceh: Perspectives of Constitutional Law and Islamic Law - Idami, Zahratul; Hirdayadi, Israr; Mukhlis, Mukhlis; Isa, Qudwatin Nisak M; Masturah, Siti Ghaisani (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Higher education actually plays a role in strengthening national insight and nationalism in an academic framework as evidenced by efforts to prevent radicalism. This study examines the efforts of universities in preventing several universities in Aceh, namely Syiah Kuala University, Ar-Raniry State Islamic University, Malikussaleh University, Teuku Umar University and Muhammadiyah Aceh University. This research uses empirical legal methods with an approach to constitutional law and Islamic law. The data collection techniques used were in-depth interviews and literature studies. The results of this study show that radicalism is not found in higher education institutions in Aceh. Internal and external factors can influence the difficulty of finding radicalism. Internal factors include a diverse understanding of university elements about radicalism and a lack of religious understanding among students and leaders. The external factor is that there is no regulation that provides indicators of radicalism and students joining various organizations, and it is difficult to distinguish which ones are radical. However, universities have made efforts to prevent radicalism, namely; prevent lecturers and students from having extreme ideologies, strengthen the concept of nationalism and nationality and encourage students to participate in non-academic activities. In the context of constitutional law, this effort is a strategic policy carried out by the state through universities to create stability and peace. In addition, in the context of Islamic law, these efforts are in line with the objectives of Sharia, namely preventing harm and creating the benefit of the nation and state.